2012
DOI: 10.1016/j.jcin.2012.03.016
|View full text |Cite
|
Sign up to set email alerts
|

A Global Risk Approach to Identify Patients With Left Main or 3-Vessel Disease Who Could Safely and Efficaciously Be Treated With Percutaneous Coronary Intervention

Abstract: In comparison with the SXscore, the Global Risk, with a simple treatment algorithm, substantially enhances the identification of low-risk patients who could safely and efficaciously be treated with CABG or PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
62
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 57 publications
3
62
1
3
Order By: Relevance
“…These findings also are in contrast to a substudy of the SYNTAX trial 18 that suggested patients with high clinical comorbidity, i.e. additive EuroSCORE ≥ 6 with 3VD irrespective of the anatomical complexity (SYNTAX score), 19 might derive a prognostic benefit from undergoing CABG rather than PCI provided an acceptable threshold of operative risk is not exceeded.…”
Section: After Syntaxcontrasting
confidence: 93%
See 3 more Smart Citations
“…These findings also are in contrast to a substudy of the SYNTAX trial 18 that suggested patients with high clinical comorbidity, i.e. additive EuroSCORE ≥ 6 with 3VD irrespective of the anatomical complexity (SYNTAX score), 19 might derive a prognostic benefit from undergoing CABG rather than PCI provided an acceptable threshold of operative risk is not exceeded.…”
Section: After Syntaxcontrasting
confidence: 93%
“…[13][14][15][16] However, the SYNTAX score is open to criticism since it relies solely on scoring coronary anatomy and does not take potentially important prognostic information into consideration in the absence of clinical factors. 17,18 Consequently, several risk stratification tools have attempted to merge the SYNTAX score with clinically based risk scores to improve the risk stratification of patients with 3VD/ULMCA disease undergoing CABG or PCI compared with the SYNTAX score alone. Examples include the Clinical SYNTAX score (a combination of the SYNTAX score and the modified ACEF score [i.e.…”
Section: After Syntaxmentioning
confidence: 99%
See 2 more Smart Citations
“…The seminal study by Gould et al reported that hyperemic flow begins to decline in the presence of stenosis with a reduction in diameter larger than 50% 1. This cut‐off value has been used for the threshold of inducible ischemia; therefore, it is accepted as the gold standard for guiding revascularization, validating noninvasive testing, and evaluating outcomes after revascularization strategies 2, 3, 4. However, cumulative evidence suggests that angiographically determined anatomical stenosis severity often underestimates or overestimates the functional significance of lesions 5, 6, 7.…”
Section: Introductionmentioning
confidence: 99%